OP0200-HPR How many subjective measurement tools are needed in knee osteoarthritis assessment?. (23rd January 2014) - Martin-Martin, L.; Magro-Checa, C.; Valenza, C.; Caracuel-Martinez, J.-C.; Castellote-Caballero, Y.; Fajardo-Rodriguez, M.; Valenza, G.
Abstract : Background: Osteoarthritis (OA) is the most common arthritis worldwide. OA ischaracterized by erosion and loss of articular cartilage accompanied by hypertrophic changes in neighboring bone that result in pain, stiffness, and gradual deterioration of mobility 1 . Nowadays is the most common cause of physical disability among older patients. Therefore, different instruments have been developed to evaluate the impact of OA on functioning and quality of life of patients, among them EQ-5D and WOMAC 2 Objectives: To determine the association and correlation among common subjective measuring toolsfor knee osteoarthritis: EQ, WOMAC and VAS Methods: 120 patients with radiologically confirmed knee osteoarthritis were evaluated with Visual Analogue Scale (VAS) for pain, Western Ontario and McMaster Osteoarthritis Index (WOMAC) for functional status, and EQ-5D for Health related quality of life. That measures werecompared and the concordance (Kappa Index) among the three guides calculated Results: An 80% of the sample were women, mean (SD) age 64, 11 (10, 361) and BMI 31, 40 kg/m 2 (5, 3). Radiographic severity mean (SD) was 2, 63 (0, 685) and 75% had more affected joints besides knee. Mean (SD) standardized tools scores were: EVA 6, 46 (2, 3 SD); EQ-5D 0, 58 (0, 23); EQ-5D VAS 56, 6 (16, 9); WOMAC pain 8, 97 (3, 7); WOMAC stiffness 3 (2); WOMAC function 29, 5 (12, 8) and WOMAC global 41, 5 (16, 86). People who reported higher scores on EVA, did the same in pain, function and global areas of WOMAC and had worse scores in quality of life instrument (EQ-5D) likewise. EQ-5D and WOMAC had also a significant association Conclusions: The high degree of association between WOMAC and EQ suggests that only one of them would be enough to get general health status data. EVA was mismatched respect to the others instruments nevertheless, so it could be useful variable to add information. We would need inquireif the different point in time which every tool takes in account to collect patient information influences these results References: Sevick MA, Miller GD, Loeser RF, Williamson JD, Messier SP Xie F, Pullenayegum EM, Li SC, Hopkins R, Thumboo J, Lo NNValue Health Disclosure of Interest: None Declared